Assisted reproduction: legal and ethical aspects. Scientific production in on-line journals - Lins dos Santos, Sarah; Ribeiro Santos, Sérgio (Acta Bioethica, 2013)
Objectives: to examine the modalities of scientific production on legal and ethical aspects of assisted reproduction between 2006-2011; to identify the areas and training of researchers involved; to investigate the points of view includedin the studies. The source were articles included in the Virtual Health Library. The universe was 884 publications, 8 of which were part of the sample. The empirical analysis demonstrated that the majority were original publications. Regardingknowledge area, 12,80% belonged to medicine and 2,25 % to Law. Two categories were identified: medical and juridical understanding and bioethics. The study revealed an amount of non scientific literature on bioethical aspects of assisted reproduction. Some studies were identified presenting innovative proposals on valorization of the right to life y the safeguard of fundamental human rights.